2020
DOI: 10.3390/microorganisms8040475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Protease on Growth Performance and Excreta Microbiome of Broiler Chicks

Abstract: One-day-old chicks were assigned one of four dietary treatments in a 2 × 2 factorial design in which the main effects were diet (adequate vs. low protein) and the addition of protease (0 vs. 200 g/1000 kg of feed). Chick performance (days 0–14) was recorded and their excreta were analyzed for short chain fatty acids, ammonia, and composition of the microbiota using 16S rRNA gene sequencing. Birds fed the low protein diet had lower body weight gain and poorer overall feed conversion ratio (FCR) (p ≤ 0.04); howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
4
14
2
Order By: Relevance
“…It was found that microbial richness was overall not changed in terms of observed OTUs and Chao1 index due to diet. Similar to the outcomes of the present trial, the Shannon index reported by Lourenco et al [ 24 ] displayed no difference with enzyme inclusion, indicating a similar microbial profile across all treatment groups, in terms of species and richness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was found that microbial richness was overall not changed in terms of observed OTUs and Chao1 index due to diet. Similar to the outcomes of the present trial, the Shannon index reported by Lourenco et al [ 24 ] displayed no difference with enzyme inclusion, indicating a similar microbial profile across all treatment groups, in terms of species and richness.…”
Section: Discussionsupporting
confidence: 88%
“…As shown in Table 6 , the relative abundance of bacteria was predominantly from the phylum Firmicutes, followed by Proteobacteria, Bacteroidetes, Actinobacteria, and other phyla. This trend has been also reported by Lourenco et al [ 24 ] and Danzeisen et al [ 25 ], with both finding Firmicutes as the predominant phylum in the chicken cecum content. Figure 5 reveals that of the 79 identified taxa, three were unique, 10 panned across several treatment groups, and the remaining 66 were core to all treatment groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Due to the public concern of antibiotics use in poultry feed ( KeepAntibioticsWorking.com, 2003 ; Hao et al., 2014 ; Hoelzer et al., 2017 ), banning antibiotics as growth promoters represent a significant challenge for poultry meat production. The dilemma has led to the imperative to identify new approaches or alternatives to remedy this problem ( Joerger, 2003 ; Gaggìa et al., 2010 ; Marshall and Levy, 2011 ; Lhermie et al., 2016 ; Lourenco et al., 2020 ; Ricke et al., 2020 ). Subtherapeutic antibiotic use in poultry feed has drawn global concerns for antibiotic resistance in pathogens that are identified as human health risks, resulting in the banning of antibiotics for growth promotion in animal agriculture usage around the world ( Casewell et al., 2003 ; Van Boeckel et al., 2015 ; Ricke et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also claimed that the interaction between the protein source and enzyme supplementation had no effect on the prececal digestibility of crude protein and amino acids except for cystine. Lourenco et al [38] reported that birds fed a low protein diet exhibited lower BWG and poorer overall FCR, but these parameters remained unaffected by protease inclusion. It can thus be assumed that the effect of protease on amino acid digestibility depends on the diet composition since the feed components provide the substrate for the working of the enzymes.…”
Section: Discussionmentioning
confidence: 99%